Pemilihan Aturan Fuzzy Inference System Mamdani Menggunakan Algoritme Particle Swarm Optimization Dalam Sistem Penyiraman Otomatis Pada Tanaman Tomat - Indah Larasati; Budi Darma Setiawan; Mahendra Data (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Laboratorium Tanah Benih Balai Pengkajian Teknologi Pertanian (BPTP) East Java is one of the institutes to do some research on plant nursery. One of soil testings which have been done in Laboratorium Tanah BPTP East Java is the parameter testing soil humadity. The research laboratory, right now, is developing an automatic watering based on soil humadity sensory to predict the amount of water needed to keep the humadity of the growing seed media. This research will figure out how much water plant volume with two input variables which are the initial humadity and flushing duration using Fuzzy Inference System Mamdani method. The two variables can cause often repeated rule based fuzzy or the same rule used more than once. Thus, to prevent these things to be happened, it needs fuzzy rule base fuzzy choice by using Particle Swarm Optimization algorithm. The testing was done in ten times trials by applying the amount of particles which is 250, value of inertia quality (w), which is 0,7, combination value of C1 and C2, which are 1,4 and 1,3, and the maximum iteration, which is 2500, and then it obtained the highest fitness value is on the seventh trial, which is 0,39949 with Root Mean Square Error (RMSE) value, which is 1,50319. The result from the highest fitness value is able to change the system from 27 arrangements to eight arrangements.